1999
DOI: 10.1111/j.1469-8749.1999.tb00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome at 1 year of neonatal encephalopathy in Kathmandu, Nepal

Abstract: To determine the outcome at 1 year of neonatal encephalopathy (NE) and to estimate the possible contribution of birth asphyxia to childhood disability in a lowincome South Asian country, a prospective cohort study was undertaken in the principal maternity hospital of Kathmandu, where over 50% of local women give birth. From a total population cohort of 21 609 live births, 131 term infants with NE (after exclusion of cases associated with neonatal sepsis, congenital malformations, or primary hypoglycaemia) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
(29 reference statements)
2
17
0
2
Order By: Relevance
“…Our findings are consistent with those of Ellis et al, 10 who found that 20% of infants with neonatal encephalopathy had neurologic impairments at 1 year follow-up versus 50% in our study, though at an earlier age. The Ellis study was conducted at a single hospital in Nepal, and serial follow-up was conducted at 6 weeks, 6 months and 1 year.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are consistent with those of Ellis et al, 10 who found that 20% of infants with neonatal encephalopathy had neurologic impairments at 1 year follow-up versus 50% in our study, though at an earlier age. The Ellis study was conducted at a single hospital in Nepal, and serial follow-up was conducted at 6 weeks, 6 months and 1 year.…”
Section: Discussionsupporting
confidence: 93%
“…[5][6][7][8][9] One of the best population studies of asphyxia in a developing country reported that 18% of survivors of mild to moderate birth asphyxia had neonatal encephalopathy and permanent severe neurologic impairment. 10 Birth asphyxia was a common cause of mental retardation, cerebral palsy and other neurodevelopmental disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Longitudinal studies indicate that hypoxia and inflammation are related to CP via a pathway that includes neonatal encephalopathy, 12,35 and maternal thyroid disorders are also associated with risk of neonatal encephalopathy. 19,36 Vulnerability to neonatal encephalopathy is likely, in future, to be a fruitful subject for genetic and genomic investigation.…”
Section: Genetic and Genomic Studiesmentioning
confidence: 99%
“…Dos 20 RN incluídos neste estudo, 15 apresentaram anormalidades transitórias na avaliação neurológica e no desenvolvimento, com normalização a partir do final do segundo trimestre de vida. A evolução do neurodesenvolvimento no fi nal do primeiro ano de vida foi adequada para a idade em todos os pacientes, o que está de acordo com outros relatos na literatura que destacaram a boa evolução dos casos de EHI leve e moderada em países desenvolvidos 2,26 , no entanto sem a correlação com um exame de avaliação vascular como o Doppler.…”
Section: Discussionunclassified